(NoSNOWY MIKROSHEMOTEHNIKI (B:s (N|LEMENTY MORFOLOGII MIKRO\LEKTRONNOJ APPARATURY (B/s - (NaLEKSENKO(B, (NaNDREJ gENNADXEWI^s ((NmOSKWA (B:s (NsOW(B. (NRADIO(B,s, 1977)
(NbIBLIOGR(B. 230 (NNAZW(B.s
Keywords: (NmIKRO\LEKTRONIKA(B. (NiNTEGRALXNYE SHEMYs